Recent advances in polymer and perovskite based third-generation solar cell devices - Alhamada, T.F.; Azmah Hanim, M.A.; Saidur, R.; Nuraini, A.; Wan Hasan, W.Z.; Jung, D.W. (Elsevier Ltd, 2023)
This review article begins with a comparative overview of the configurations, materials, fabrication methods, and energy conversion efficiency of polymer and perovskite solar cells’ photovoltaic performances. Firstly, there has been a significant increase in the adoption of solar cells due to the growing need for renewable and clean energy. Among all photovoltaic technologies, polymer and perovskite solar cells have garnered considerable attention owing to their potential to be affordable, lightweight, easy to manufacture, and quick charging. Research on polymer solar cells has spanned over two decades, whereas the use of perovskite solar cells is just eight years old. This expanding topic offers a wealth of information to readers interested in polymers and perovskite. As a basic comparison, the best power conversion efficiency results are 21.6 percent for a 1 cm2 perovskite solar cell and 15.2 percent for polymer solar cells. Finally, this article recommends necessary improvements and future research areas in polymer and perovskite solar cells.